Effect of Vacuum-Packed Refrigeration Storage on Low-FatAntioxidant-Rich Kadaknath Chicken Sausages - Patel, Divyanee; Nayak, Narendra Kumar; Chauhan, Pranav; Vipin Kumar Gupta, (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
This study aimed to investigate the impact of vacuum-packed refrigeration storage on quality of low-fat-antioxidant rich Kadaknath chicken sausages. The study examined the changes in physico-chemical, microbiological properties and sensory attributes. The pH, TBA and FFA values were lower as compared to control throughout the storage. A progressive and significant (P<0.05) increment in the pH, TBA and FFA values of control as well as treatment was observed with the advancement of storage in vacuum packaged sausage. The total plate count (TPC) followed a significantly (P<0.05) increasing pattern from 0 to 28th day. Psychrotrophic count under vacuum packaging was not detected upto 21 day of storage either in control or in treatment and was detected on 28th day of storage. Lipolytic count was not detected on initial day in both control and treatment. It was detected from 7th day to 28th day of storage both in control as well as in treatment. Yeast and mold as well as coliform were not detected during the entire period of storage. The mean scores for all the sensory attributes for both control as well as low-fat antioxidant-rich sausage decreased gradually with increasing storage period. Results showed that vacuum packaging helped in preserving the antioxidant properties of the sausage, thereby extending its shelf life without compromising quality.